2009
DOI: 10.1080/07357900802672712
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Triggers Apoptosis and Bcl-2 Downregulation in MCF-7 Breast Cancer Cells

Abstract: In this report we determine the ability of ursolic acid (UA) to induce apoptosis and to modulate glucocorticoid receptor (GR) and Activator Protein-1 (AP-1) in MCF-7 cells. The UA-induced apoptosis (53 microM), the PARP cleavage, and the decrease in Bcl-2 protein (53 microM) support the notion that UA induces apoptosis through the intrinsic mitochondrial pathway. UA binds GR (relative binding affinity: 2.57) and translocates GR into nucleus, suggesting its potential as a GR modulator. UA had no effect on GRE- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 47 publications
2
80
0
Order By: Relevance
“…Research has confirmed that p53 is an important regulator of apoptosis, and its interaction with Bcl-2 or Bcl-XL results in the assembly of pro-apoptotic proteins Bax and Bak in the mitochondrial membrane to form pores, which finally causes the release of cytochrome c and other apoptotic activators from the mitochondria (37). It was reported that the mitochondrial pathway (also called the intrinsic pathway) of apoptosis is inhibited or triggered by anti-apoptotic proteins such as Bcl-2 and Bcl-xL or pro-apoptotic proteins such as Bax, Bak, Bim and Bid (38). In the present study, the downregulation of Bcl-2 expression, and the synchronously upregulated expression of Bim and Bax in the U87MG and T87G cells probably contributed to the release of cytochrome c and the following apoptotic events, which is similar to previous studies in human gastric tumor cells and breast cancer cells (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Research has confirmed that p53 is an important regulator of apoptosis, and its interaction with Bcl-2 or Bcl-XL results in the assembly of pro-apoptotic proteins Bax and Bak in the mitochondrial membrane to form pores, which finally causes the release of cytochrome c and other apoptotic activators from the mitochondria (37). It was reported that the mitochondrial pathway (also called the intrinsic pathway) of apoptosis is inhibited or triggered by anti-apoptotic proteins such as Bcl-2 and Bcl-xL or pro-apoptotic proteins such as Bax, Bak, Bim and Bid (38). In the present study, the downregulation of Bcl-2 expression, and the synchronously upregulated expression of Bim and Bax in the U87MG and T87G cells probably contributed to the release of cytochrome c and the following apoptotic events, which is similar to previous studies in human gastric tumor cells and breast cancer cells (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the interaction between Bax and Bcl‐2 leads to a loss of mitochondrial membrane potential. As a result, mitochondrial cytochrome c is released into the cytoplasm from the mitochondria and activates the caspase pathways (Dong et al., 2014; Kassi et al., 2009). In our study, OJE‐treated cells did not exhibit dramatically altered Bax mRNA levels, but the Bcl‐2 levels were certainly decreased at the highest treatment concentration (50 Όg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…A natural compound, the pentacyclic triterpenoid ursolic acid (UA) (3 b-hydroxy-urs-12-en-28-oic-acid) (Liu 1995), has been reported to be a potent inhibitor of constitutive and inducible STAT3 as well as NF-jB activation in prostate cancer cells ). The authors also showed that UA significantly suppressed the growth of prostate cancer xenografts in vivo while it was previously reported to be able to inhibit tumor promotion, metastasis, angiogenesis and proliferation of a variety of tumor cells, including human multiple myeloma cells ) melanoma cells (Manu and Kuttan 2008) and breast cancer cells (Kassi et al 2009). Predictive analysis using a virtual tumor cell platform that allows for the determining of the primary target of UA in the prostate cancer cells showed that UA mediates an increase in the apoptotic phenotype by inhibiting STAT3 as well as NF-jB activity.…”
Section: Prostate Cancermentioning
confidence: 88%